Cancer mortality risk in the Urals Cohort of Exposed Population Offspring - D. A. Zavyalov; L. Yu. Krestinina (Радиационная гигиена, 2024)
The objective of the study is to analyze solid cancer mortality and estimate the risk value of solid cancer mortality in the offspring of parents irradiated in the Southern Urals, depending on the dose to the parents' gonads as well as to conduct a preliminary assessment of the mortality risk from cancer of individual locations depending on the gonadal dose. The issue of the transgenerational effects of the human gonad exposure is still very important. There exists conclusive evidence of the presence of such effects in experimental animals. However, there is no proof of the existence of these effects in humans despite a great number of research on this subject. International scientific community and international organizations, UNSCEAR and ICRP being among them, regard this issue as the one that has not been solved yet and requires further studies. Urals Cohort of offspring of the population exposed on the Techa River and on the territory of the East Ural radioactive trace was established in the Urals research Center for Radiation medicine in 2022. The key feature of the cohort is the exclusion of the offspring with postnatal exposure. The size of the cohort as of September 2023 is 31,154 persons. The number of person-years over the whole follow-up period from 1950 through 2020 is 1 226 380. Mean dose to the gonads of mothers of all the cohort members is 41 mGy, to those of the fathers' — 35 mGy, mean combined gonad dose is 76 mGy. Over the whole follow-up period 3,774 deaths from all causes including 284 deaths from solid cancers were registered in the cohort. The mean age of the cohort members at the end of the follow-up period was 42 years. The risk of death was analyzed using Poisson regression by the programs of the EPICURE statistical software package. Three models of dose dependence were tested: linear, quadratic, and linear-quadratic models of paternal gonadal dose, maternal gonadal dose, and total gonadal dose. Mortality risk analysis of all solid cancers in the offspring cohort showed no statistically significant effect with parental gonadal dose (we have obtained positive although statistically insignificant values of solid cancers mortality risk) which is consistent with the results of other studies in human populations. At the same time, the analysis for the first time obtained a statistically significant linear dependence of the solid cancer mortality risk in offspring with father's age over 45 years depending on the dose to the father's gonads. The excess relative risk of death was 8.09/Gy, (0.51-22.93), p < 0.05. Also, for the first time, evidence of dose dependence of the mortality risk of lung cancer in male offspring on maternal gonadal dose, paternal gonadal dose, and combined gonadal dose was obtained. The values of excess relative risk of lung cancer and 95% confidence intervals according to the linear model were 5.39/Gy (0.46; 15.56) from paternal gonad dose, 4.36/Gy (0.15; 13.48) from maternal gonad dose, and - 3.95/Gy (0.55; 12.14) from combined gonad dose. Point risk estimates of lung cancer at this stage are characterized by wide confidence intervals and require additional studies to assess the influence of possible effect modifiers, but with a high degree of probability indicate the presence of dose dependence of this effect. Increasing the follow-up period and attained age, will increase the number of cancers in the future and will reduce dose response uncertainties and provide more accurate estimates of the risk of death in the offspring cohort.